1982
DOI: 10.1161/01.cir.66.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary atresia and intact ventricular septum: a revised classification.

Abstract: The dismal outlook for patients with pulmonary atresia with intact ventricular septum may be related to associated right ventricular hypoplasia. Study of 32 autopsy specimens and 46 angiocardiograms of neonates with this lesion suggested that the cavitary hypoplasia was related to massive hypertrophy of the right ventricular wall. This hypertrophy was sufficient to obliterate the trabecular and/or infundibular portion of the ventricular cavity entirely in one-third of the cases; this observation forms the basi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(68 citation statements)
references
References 21 publications
0
66
0
1
Order By: Relevance
“…3,6 -8 Additional factors likely contribute to persistent RV diastolic dysfunction in these patients. Endocardial and myocardial abnormalities of the right ventricle are well documented in PAIVS, which include massive hypertrophy, 11 extensive myocardial fiber disarray, 12 and endocardial fibroelastosis. While growth in RV size has been shown to occur after RV decompression, 6,7 complete normalization of the histologic abnormalities seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 -8 Additional factors likely contribute to persistent RV diastolic dysfunction in these patients. Endocardial and myocardial abnormalities of the right ventricle are well documented in PAIVS, which include massive hypertrophy, 11 extensive myocardial fiber disarray, 12 and endocardial fibroelastosis. While growth in RV size has been shown to occur after RV decompression, 6,7 complete normalization of the histologic abnormalities seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
“…The dismal outlook in this condition has been attributed to the associated right ventricular hypoplasia. 4 In a recent anatomic and angiographic study, 5 we reported that cavitary hypoplasia in PA:IVS is related to massive hypertrophy of the right ventricular wall and proposed a classification of the condition based on the tripartite approach to right ventricular morphology. We distinguished three types of ventricles: those with generalized cavitary hypoplasia, those without a trabecular portion to the cavity and those in which both trabecular and infundibular portions are entirely overgrown by hypertrophied myocardium.…”
mentioning
confidence: 99%
“…According to the type of right ventricular morphology on the angiocardiographic study 44 , the 31 patients were divided into 3 groups: group A) comprised 16 patients with tripartite right ventricular morphology (inlet portion, trabecular portion, and outlet portion). In 1 patient, the tricuspid valve was dysplastic ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…pulmonary atresia, ductus arteriosus, congenital heart disease, prognostic factors, pulmonary valvotomy Right ventriculography performed in the caudocranial and lateral projections aimed at evidencing: 1) the degree of tricuspid regurgitation; 2) the diameter of the tricuspid valve 42 ; 3) presence of coronary-cavitary connections and right ventricular-dependent coronary circulation (severe proximal stenoses in the native coronary territory, mainly anterior descending and circumflex arteriescomplete obstructions in proximal points of the native coronary circulation -fistula between the native coronary territory and the right ventricle -absence of connection of the left coronary artery with the aorta, and the origin of the pulmonary artery); and 4) right ventricular morphology, according to Goor and Lillehei 43 and Bull et al 44 . Left ventriculography performed in the elongated left anterior oblique projection aimed at the following: 1) assessment of the size and configuration of the left ventricle; 2) opacity of the aorta and, based on its visualization, determination of the angle formed by the ductus arteriosus and the descending aorta; 3) visualization of the right and left coronary arteries and establishment of the type of ventricular perfusion (anterograde: from the aorta to the right ventricle during diastole).…”
Section: Introductionmentioning
confidence: 99%